El dolor que nos une : el tercer caso del sargento Aector McAvoy - Mark, David John, 1977-; Porras Sánchez, María; Mark, David John, 1977- ([Madrid] : Siruela, 2015)
Detective Sergeant Aector McAvoy returns for another darkly enthralling case in Sorrow Bound, the third installment of David Mark's internationally acclaimed and bestselling series.
Online resource; title from ePub title page (Digitalia, viewed April 21, 2017)
Keywords: Murder -- Investigation -- Fiction; Drugs -- Fiction; Survival -- Fiction; Detective and mystery fiction; Noir fiction; Electronic books